Spatial and seasonal changes in monitoring water quality of Savanna River system - Aliyu, Adamu Gaddafi; Jamil, Nor Rohaizah; Adam, Mohd Bakri; Zulkeflee, Zufarzaana (Springer, 2020)
Using 15 sampling stations, study was conducted to assess the water quality parameters of samples collected from River Galma, Zaria, Northwestern Nigeria, in wet and dry seasons. This was achieved using analysis of independent samples test (t-test), hierarchical cluster analysis (HCA), and principal component analysis (PCA) techniques. Analysis of the t-test results shows that, out of the 18 water quality parameters analyzed, 9 parameters were statistically significant (p < 0.05), while the remaining parameters were statistically significant at p > 0.05 for both seasons and all the concentration of the water quality parameters results increases during dry season, which may be attributed to water evaporation and absence of rainfall. HCA identified 4 and 3 different groups in wet season (WS) and dry seasons (DS) from 18 water quality parameters, which indicate that the variation in water quality are due to natural and anthropogenic processes. Two components resulted from PCA analysis from both WS and DS. PCA explained 79.33% of the total variance in the variables which are included in the component in WS and 80.09% of the total variance in the variables which are included in the component in DS, in which the major sources of pollution are related to agriculture and other human activities. From this study, it shows that application of environmetric multivariate techniques are significant to environmental management and the result will help stakeholders in decision making toward sustainable management support of the river system.